Optical film
By using specific polycarbonate-based polyurethane to form an easy-adhesive layer on the surface of the acrylic resin film, the problems of reduced adhesion and whitening of the easy-adhesive layer in high temperature and high humidity environment are solved, and the efficient moisture- and heat-resistant properties of the optical film are achieved.
Patent Information
- Application Number
- CN202380069606.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when the acrylic resin film is used in a high temperature and high humidity environment, the adhesion property is reduced and the adhesive layer is whitened due to extension, resulting in deterioration of optical characteristics.
A specific polycarbonate-based polyurethane is used as the main component of the easy-adhesive layer, with a weight average molecular weight of more than 200,000 and less than 2.5 million. An easy-adhesive layer is formed on the surface of the resin film to improve adhesion and high-temperature and high-humidity resistance.
The initial performance maintenance during long-term use in high-temperature and high-humidity environments is achieved, and the whitening of the easy adhesive layer and the reduction of optical characteristics are avoided, which significantly improves the adhesion and moisture and heat resistance of the acrylic resin film.
Smart Images

Figure CN119895301A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical film comprising a resin film containing a (meth)acrylic resin as a main component and an easy-adhesion layer laminated on one surface thereof. Background Art
[0002] It is known that acrylic resin films made of (meth)acrylic polymers represented by polymethyl methacrylate (PMMA) have excellent optical properties such as light transmittance, and have an excellent balance between mechanical strength and molding processability. Therefore, acrylic resin films have been used for optical-related purposes in recent years, and the application of optical films assembled in image display devices such as liquid crystal display devices (LCD), liquid crystal displays (PDP), and organic EL display devices (OLED) has been developing.
[0003] Optical films are usually used in a state of being stacked with other functional films. For example, a polarizer protective film, which is a type of optical film, is used in an image display device in the state of a polarizing plate stacked with the polarizer via an adhesive layer composed of a hydrophilic adhesive or an ultraviolet curing adhesive on at least one side of the polarizer. Therefore, the adhesion with the stacked polarizer must be good.
[0004] However, acrylic resin films have poor adhesion to hydrophilic adhesives or ultraviolet curing adhesives and insufficient adhesion to polarizers. Therefore, a method has been proposed to provide an easy-adhesion layer having an adhesion-assisting resin (adhesive resin) such as polyester, acrylic acid, or urethane as a main component on the surface of the acrylic resin film to impart easy adhesion to the acrylic resin film.
[0005] For example, Patent Document 1 describes an optical film having an easy-adhesion layer formed on an acrylic film, wherein the easy-adhesion layer is composed of an easy-adhesion composition comprising a polyurethane polymer having a weight average molecular weight of 10,000 to 100,000 obtained by reacting polycarbonate diol and isocyanate, and describes that an optical film with excellent adhesion is obtained by using the polyurethane polymer as the easy-adhesion composition.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2010-63773 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] Incidentally, in recent years, portable devices using image display devices such as LCDs are used in various environments both indoors and outdoors, and are sometimes required to have moisture and heat resistance that can withstand high temperature and high humidity environments. Polarizing plates used for such applications are required to have high adhesion that does not cause interlayer peeling even under high temperature and high humidity conditions (e.g., 85°C, 85%RH).
[0011] However, the optical film having an easy-adhesion layer disclosed in the above document initially exhibits good adhesion, but when used for a long time under high temperature and high humidity, the adhesion inevitably decreases, and there is a problem that the initial performance (initial adhesion) cannot be maintained for a long time.
[0012] It should be noted that the acrylic resin film of the substrate is subjected to a stretching treatment for the purpose of adjusting the mechanical strength, etc., but from the viewpoint of improving the manufacturing efficiency of the optical film, before the continuously conveyed long acrylic resin film before stretching is supplied to the stretching device, it is preferred that a coating liquid of an easy-adhesion composition is applied to the surface of the acrylic resin film before stretching, and the coating is dried and the acrylic resin film before stretching is stretched in the preheating zone and stretching zone of the stretching device. However, when the easy-adhesion composition disclosed in the above-mentioned document is used, when the easy-adhesion layer formed on the surface of the acrylic resin film is stretched, there is a problem that the easy-adhesion layer whitens, causing a decrease in optical properties (light transmittance, haze, etc.).
[0013] The present invention has been made in view of these problems, and an object of the present invention is to provide an optical film which can suppress the initial performance degradation during long-term use under high temperature and high humidity, and can suppress the whitening of the easy-adhesion layer and the degradation of optical characteristics due to stretching or the like.
[0014] The present inventors have actively examined an easy-adhesion layer that has excellent adhesion to an acrylic resin film and can suppress initial performance degradation and whitening of the easy-adhesion layer under high temperature and high humidity. As a result, they have found that the above-mentioned technical problems can be solved by using a specific polycarbonate-based polyurethane as the binder resin of the easy-adhesion layer, thereby completing the present invention.
[0015] According to the present invention, there is provided
[0016] (1) An optical film, characterized in that it comprises: a resin film containing an acrylic resin as a main component; and an easy-adhesion layer laminated on one surface of the resin film, the easy-adhesion layer containing a polycarbonate-based polyurethane as a main component, the weight average molecular weight of the polycarbonate-based polyurethane being not less than 200,000 and not more than 2.5 million, and the shear storage elastic modulus (E') at 25°C being not less than 100,000 and not more than 100,000. 25 ) and the shear storage elastic modulus (E') at 85 °C 85 ) of the shear storage elastic modulus (E' 25 / E' 85 ) is less than 5.
[0017] (2) The optical film according to (1), wherein the polycarbonate-based polyurethane has a shear loss elastic modulus (E”) at 25°C. 25 ) and shear loss elastic modulus (E') at 85°C 85 ) shear loss elastic modulus ratio (E') 25 / E” 85 ) is less than 2.
[0018] (3) The optical film according to (1), wherein the shear loss tangent (tan δ) of the polycarbonate-based polyurethane at 25°C is 25 ) is less than 0.1.
[0019] (4) The optical film according to (1), wherein the shear storage elastic modulus (E') of the polycarbonate-based polyurethane at 25°C is 25 ) is greater than 500 MPa and less than 1500 MPa.
[0020] (5) The optical film according to (1), wherein the polycarbonate-based polyurethane has a shear loss modulus of elasticity (E”) at 25°C. 25 ) is greater than 40 MPa and less than 150 MPa.
[0021] (6) The optical film according to (1), wherein the acrylic resin has at least one selected from the group consisting of a glutarimide unit, a lactone ring unit, a maleic anhydride unit, a maleimide unit, and a glutaric anhydride unit.
[0022] (7) A polarizing plate, characterized in that the optical film according to any one of (1) to (6), an adhesive layer, and a polarizer are laminated in this order such that the easy-adhesion layer is in contact with the adhesive layer.
[0023] Effects of the Invention
[0024] The optical film of the present invention has excellent adhesion to acrylic resin films and other components such as polarizers by using a specific polycarbonate-based polyurethane as the adhesive resin of the easy-adhesion layer. In addition, the optical film of the present invention can suppress the initial performance degradation when used for a long time under high temperature and high humidity, and can suppress the whitening of the easy-adhesion layer due to stretching, etc., and can suppress the degradation of optical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional view showing an example of the optical film of the present invention.
[0026] Figure 2 This is a cross-sectional view showing an example of the polarizing plate of the present invention. DETAILED DESCRIPTION
[0027] Hereinafter, the present invention will be described in detail. In addition, the present invention is not limited to the following aspects, and various aspects can be made within the scope of exerting the effects of the present invention.
[0028] [Overview of optical films]
[0029] The optical film of the present invention includes a resin film containing an acrylic resin as a main component and a bonding layer containing a polycarbonate polyurethane as a main component on one surface of the resin film.
[0030] [Resin film]
[0031] The resin film is composed of a thermoplastic resin with acrylic resin as the main component. Here, the so-called "main component" means that the composition ratio of the components constituting the resin film is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and particularly preferably 95% by weight or more.
[0032] As the acrylic resin, any appropriate acrylic resin can be used. Representative acrylic resins contain (meth) alkyl acrylate as a main component as a monomer unit. The so-called "(meth) acrylic acid" in this specification refers to acrylic acid and / or methacrylic acid. As the (meth) alkyl acrylate constituting the main skeleton of the (meth) acrylic resin, examples include linear or branched alkyl groups with 1 to 18 carbon atoms. These can be used alone or in combination. In addition, any appropriate copolymerization monomer can also be introduced into the (meth) acrylic resin by copolymerization. The type, quantity, copolymerization ratio, etc. of such copolymerization monomers can be appropriately set according to the purpose.
[0033] The acrylic resin preferably has at least one selected from a glutarimide unit, a lactone ring unit, a maleic anhydride unit, a maleimide unit, and a glutaric anhydride unit. The acrylic resin having a lactone ring unit is described in, for example, Japanese Patent Publication No. 2008-181078, and the description of the publication is cited as a reference in this specification. The glutarimide unit is preferably represented by the following general formula (1):
[0034] .
[0035] In the general formula (1), R 1 and R 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.1 and R 2 are independently a hydrogen atom or a methyl group, R 3 is a hydrogen atom, a methyl group, a butyl group or a cyclohexyl group. 1 is methyl, R 2 is a hydrogen atom, R 3 It is methyl.
[0036] The (meth)acrylic acid alkyl ester is typically represented by the following general formula (2):
[0037] .
[0038] In general formula (2), R 4 represents a hydrogen atom or a methyl group, R 5 represents a hydrogen atom or a substituted aliphatic or alicyclic hydrocarbon group having 1 to 6 carbon atoms. Examples of substituents include halogen and hydroxyl. Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate and 2,3,4,5-tetrahydroxypentyl (meth)acrylate. In the general formula (2), R 5 A hydrogen atom or a methyl group is preferred. Therefore, a particularly preferred (meth)acrylic acid alkyl ester is methyl acrylate or methyl methacrylate.
[0039] The acrylic resin may contain only a single glutarimide unit, or may contain R 1 , R 2 and R 3 Different multiple glutarimide units. The content of the glutarimide units in the acrylic resin is preferably 2 mol% to 50 mol%, more preferably 2 mol% to 45 mol%, further preferably 2 mol% to 40 mol%, particularly preferably 2 mol% to 35 mol%, and most preferably 3 mol% to 30 mol%. If the content is less than 2 mol%, the effects derived from the glutarimide units (such as high optical properties, high mechanical strength, excellent adhesion to polarizers, and thinning) may not be fully exerted. If the content exceeds 50 mol%, for example, heat resistance and transparency may be insufficient.
[0040] The acrylic resin may contain only a single (meth)acrylic acid alkyl ester unit, or may contain R 4 and R 5Different multiple (meth) alkyl acrylate units. The content ratio of the (meth) alkyl acrylate unit in the acrylic resin is preferably 50 mol% to 98 mol%, more preferably 55 mol% to 98 mol%, further preferably 60 mol% to 98 mol%, particularly preferably 65 mol% to 98 mol%, and most preferably 70 mol% to 97 mol%. If the content ratio is less than 50 mol%, the effect (such as high heat resistance and high transparency) derived from the (meth) alkyl acrylate unit may not be fully exerted. If the content ratio is more than 98 mol%, the resin is brittle and easy to break, and it is possible that the high mechanical strength cannot be fully exerted, and the productivity is poor.
[0041] The acrylic resin may contain units other than the glutarimide unit and the (meth) alkyl acrylate unit. In one embodiment, the acrylic resin may contain, for example, 0 to 10% by weight of an unsaturated carboxylic acid unit that does not participate in the intramolecular imidization reaction described later. The content of the unsaturated carboxylic acid unit is preferably 0 to 5% by weight, more preferably 0 to 1% by weight. If the content is within this range, transparency, retention stability and moisture resistance can be maintained.
[0042] In one embodiment, acrylic resin can contain copolymerizable vinyl monomer units (other vinyl monomer units) other than the above. For example, other vinyl monomers are acrylonitrile, methacrylonitrile, ethacrylonitrile, allyl glycidyl ether, maleic anhydride, itaconic anhydride, N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide, aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminoethyl methacrylate, ethylaminopropyl methacrylate, cyclohexylaminoethyl methacrylate, N-vinyldiethylamine, N-acetylvinylamine, allylamine, methylallylamine, N-methylallylamine, 2-isopropenyl oxazoline, 2-vinyl oxazoline, 2-acryloyl oxazoline, N-phenylmaleimide, methyl phenylaminoethyl ester, styrene, α-methylstyrene, p-glycidyl styrene, p-aminostyrene, 2-styryl oxazoline, etc. These can be used alone or in combination. Preferably, the styrene monomers are styrene, α-methylstyrene, etc. The content of other vinyl monomer units is preferably 0 to 5% by weight, more preferably 0 to 1% by weight, and further preferably 0 to 0.1% by weight. If it is within this range, it is possible to suppress the unnecessary phase difference and the reduction of transparency.
[0043] The imidization rate in the acrylic resin is preferably 2.5% to 20.0%. If the imidization rate is within this range, a resin with excellent heat resistance, transparency and molding processability can be obtained, which can prevent the occurrence of scorching and reduction of mechanical strength during film molding. In the above-mentioned acrylic resin, the imidization rate is expressed as the ratio of glutarimide units to (meth) alkyl acrylate units. This ratio can be obtained from the NMR spectrum, IR spectrum, etc. of the acrylic resin. In this embodiment, the imidization rate can be expressed using 1 HNMR BRUKER AvanceIII (400MHz) was used to analyze the resin 1 More specifically, the peak area of O-CH3 protons derived from (meth) alkyl acrylate around 3.5 to 3.8 ppm is defined as A, and the peak area of N-CH3 protons derived from glutarimide around 3.0 to 3.3 ppm is defined as B, and the result is determined by the following formula.
[0044] Imidization rate Im(%)={B / (A+B)}×100
[0045] The acid value of the acrylic resin is preferably 0.10mmol / g to 0.50mmol / g. If the acid value is within this range, a resin having excellent balance of heat resistance, mechanical properties and molding processability can be obtained. If the acid value is too small, problems such as cost increase due to the use of a denaturant to adjust to the desired acid value and the generation of a gel-like substance due to the residue of the denaturant may occur. If the acid value is too large, foaming is easily caused during film molding (e.g., during melt extrusion), and there is a tendency for the productivity of the molded product to decrease. In the above-mentioned acrylic resin, the acid value is the content of the carboxylic acid unit and the carboxylic anhydride unit in the acrylic resin. In this embodiment, the acid value can be calculated by the titration method described in, for example, WO2005 / 054311 or Japanese Patent Publication No. 2005-23272.
[0046] The weight average molecular weight of the acrylic resin is preferably 1,000 to 2,000,000, more preferably 5,000 to 1,000,000, further preferably 10,000 to 500,000, particularly preferably 50,000 to 500,000, and most preferably 60,000 to 150,000. The weight average molecular weight can be determined by polystyrene conversion using a gel permeation chromatograph (GPC system, manufactured by TOSOH). It should be noted that tetrahydrofuran can be used as a solvent.
[0047] The Tg (glass transition temperature) of the acrylic resin is preferably 110°C or higher, more preferably 115°C or higher, further preferably 120°C or higher, particularly preferably 125°C or higher, and most preferably 130°C or higher. If Tg is 110°C or higher, a polarizing plate containing a substrate film obtained from these resins tends to have excellent durability. The upper limit of Tg is preferably 300°C or lower, more preferably 290°C or lower, further preferably 285°C or lower, particularly preferably 200°C or lower, and most preferably 160°C or lower. If Tg is within this range, the moldability can be excellent.
[0048] The acrylic resin can be produced, for example, by the following method. The method comprises: (I) copolymerizing an alkyl (meth)acrylate monomer corresponding to the alkyl (meth)acrylate unit represented by the general formula (2) with an unsaturated carboxylic acid monomer and / or a precursor monomer thereof to obtain a copolymer (a); and (II) treating the copolymer (a) with an imidizing agent to carry out an intramolecular imide reaction of the alkyl (meth)acrylate monomer unit and the unsaturated carboxylic acid monomer and / or a precursor monomer unit thereof in the copolymer (a), thereby introducing a glutarimide unit represented by the general formula (1) into the copolymer.
[0049] Examples of unsaturated carboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, α-substituted acrylic acid, and α-substituted methacrylic acid. Examples of precursor monomers thereof include acrylamide and methacrylamide. These may be used alone or in combination. Preferred unsaturated carboxylic acid monomers are acrylic acid or methacrylic acid, and preferred precursor monomers are acrylamide.
[0050] As a method for treating the copolymer (a) with an imidizing agent, any appropriate method can be used. As specific examples, a method using an extruder and a method using a batch reaction tank (pressure vessel) are exemplified. The method using an extruder includes using an extruder to heat and melt the copolymer (a), and treating it with an imidizing agent. In this case, as an extruder, any suitable extruder can be used. As specific examples, a single-axis extruder, a double-axis extruder, and a multi-axis extruder are exemplified. In the method using a batch reaction tank (pressure vessel), any appropriate batch reaction tank (pressure vessel) can be used.
[0051] As the imidizing agent, any suitable compound can be used as long as it can generate the glutarimide unit represented by the general formula (1). Specific examples of the imidizing agent include amines containing aliphatic hydrocarbon groups such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, amines containing aromatic hydrocarbon groups such as aniline, benzylamine, toluidine, trichloroaniline, and amines containing alicyclic hydrocarbon groups such as cyclohexylamine. Furthermore, urea compounds that generate these amines by heating, for example, can also be used. Examples of urea compounds include urea, 1,3-dimethylurea, 1,3-diethylurea, and 1,3-dipropylurea. The imidizing agent is preferably methylamine, ammonia, and cyclohexylamine, and more preferably methylamine. In the imidization, in addition to the above-mentioned imidizing agent, a dead cycle accelerator can also be added as needed. The amount of the imidizing agent used in the imidization is preferably 0.5 to 10 parts by weight, more preferably 0.5 to 6 parts by weight, relative to 100 parts by weight of the copolymer (a). When the amount of the imidizing agent used is less than 0.5 parts by weight, the desired imidization rate cannot be achieved in many cases. As a result, the heat resistance of the obtained resin is extremely insufficient, and there are cases where appearance defects such as scorching after molding are induced. When the amount of the imidizing agent used exceeds 10 parts by weight, the imidizing agent will remain in the resin, and there are cases where the imidizing agent induces appearance defects such as scorching after molding and foaming.
[0052] If necessary, in addition to the above-mentioned imidization, the method for producing an acrylic resin may also include treatment with an esterifying agent. Examples of the esterifying agent include dimethyl carbonate, 2,2-dimethoxypropane, dimethyl sulfoxide, triethyl orthoformate, trimethyl orthoacetate, trimethyl orthoformate, diphenyl carbonate, dimethyl sulfate, methyl toluenesulfonate, methyl trifluoromethanesulfonate, methyl acetate, methanol, ethanol, methyl isocyanate, p-chlorophenyl isocyanate, dimethylcarbodiimide, dimethyl tert-butylsilane chloride, isopropenyl acetate, dimethyl urea, tetramethylammonium hydroxide, dimethyldiethoxysilane, tetra-n-butoxysilane, dimethyl (trimethylsilyl) phosphite, trimethyl phosphite, trimethyl phosphate, tricresyl phosphate, diazomethane, ethylene oxide, propylene oxide, cyclohexene oxide, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, and benzyl glycidyl ether. Among these, dimethyl carbonate is preferred from the viewpoint of cost and reactivity. The amount of the esterifying agent added can be set so that the acid value of the acrylic resin becomes a desired value.
[0053] The resin film may also use acrylic resin and other resins in combination. That is, the monomer components constituting the acrylic resin are copolymerized with the monomer components constituting other resins, and the copolymer is provided for the film formation described later; the blend of acrylic resin and other resins may also be provided for film formation. Examples of other resins include other thermoplastic resins such as styrene resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyetheretherketone, polyester, polysulfone, polyphenylene ether, polyacetal, polyimide, polyetherimide, and the like, and thermosetting resins such as phenolic resins, melamine resins, polyester resins, silicone resins, and epoxy resins. The type and amount of the resins used in combination may be appropriately set according to the purpose and the desired properties of the resulting film. For example, a styrene resin (preferably an acrylonitrile-styrene copolymer) may be used in combination as a phase difference controller. When an acrylic resin and other resins are used together, the content of the acrylic resin in the blend of the acrylic resin and other resins is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. If the content is less than 50% by weight, the high heat resistance and high transparency inherent in the acrylic resin may not be fully reflected.
[0054] The resin film may also be a core-shell particle prepared in an acrylic resin, preferably 5 to 50 parts by weight, more preferably 5 to 40 parts by weight relative to 100 parts by weight of the acrylic resin. The core-shell particle typically has a core composed of a rubbery polymer and a covering layer composed of a glassy polymer and covering the core. The core-shell particle may also have one or more layers composed of a glassy polymer as the innermost layer or intermediate layer.
[0055] The Tg of the rubber polymer constituting the core is preferably 20°C or less, more preferably -60°C to 20°C, and further preferably -60°C to 10°C. When the Tg of the rubber polymer constituting the core exceeds 20°C, the mechanical strength of the acrylic resin may not be sufficiently improved. The Tg of the glassy polymer (hard polymer) constituting the covering layer is preferably 50°C or more, more preferably 50°C to 140°C, and further preferably 60°C to 130°C. When the Tg of the glassy polymer constituting the covering layer is lower than 50°C, the heat resistance of the acrylic resin may be reduced.
[0056] The content ratio of the core in the core-shell type particle is preferably 30% to 95% by weight, and more preferably 50% to 90% by weight. The ratio of the glassy polymer layer in the core is 0% to 60% by weight, preferably 0% to 45% by weight, and more preferably 10% to 40% by weight, relative to the total weight of the core (100% by weight). The content ratio of the covering layer in the core-shell type particle is preferably 5% to 70% by weight, and more preferably 10% to 50% by weight.
[0057] Details of the rubbery polymer constituting the core of the core-shell particles, the glassy polymer (hard polymer) constituting the coating layer, their polymerization methods, and other configurations are described, for example, in Japanese Unexamined Patent Publication No. 2016-33552, the contents of which are incorporated herein by reference.
[0058] The thickness of the resin film is preferably 5 μm or more, more preferably 8 μm or more, further preferably 10 μm or more, preferably 200 μm or less, more preferably 100 μm or less, further preferably 70 μm or less, and particularly preferably 60 μm or less. By setting the thickness of the resin film to be above the lower limit of the above range, the mechanical strength of the resin film can be increased. In addition, by setting it to be below the upper limit, the thickness of the resin film can be reduced.
[0059] As a method for forming a resin film, any suitable method can be adopted. As specific examples, cast coating method (such as cast method), extrusion molding method, injection molding method, compression molding method, transfer molding method, blow molding method, powder molding method, FRP molding method, calendaring molding method and hot pressing method are exemplified. Extrusion molding method or casting coating method is preferred. The reason is that the smoothness of the obtained film can be improved and good optical uniformity can be obtained. Extrusion molding method is particularly preferred. Among them, based on the viewpoint of the productivity of the film and the ease of subsequent stretching treatment, extrusion molding method using a T-die is preferred. The molding conditions can be appropriately set according to the composition and type of the resin used, the characteristics required for the obtained film, etc.
[0060] As the stretching method, any appropriate stretching method and stretching conditions (such as stretching temperature, stretching ratio, stretching speed, stretching direction) can be adopted. Specific examples of the stretching method include free end stretching, fixed end stretching, free end shrinking, and fixed end shrinking. These can be used alone, simultaneously, or successively.
[0061] The stretching direction can be an appropriate direction according to the purpose. Specific examples include the length direction, width direction, thickness direction and oblique direction. The stretching direction can be one direction (uniaxial stretching), two directions (biaxial stretching), or more than three directions. In the embodiment of the present invention, uniaxial stretching in the length direction, biaxial stretching in the length direction and the width direction at the same time, and biaxial stretching in the length direction and the width direction successively can be representatively adopted. Biaxial stretching (simultaneous or successively) is preferred, which is easy to control the in-plane phase difference and easy to achieve optical isotropy.
[0062] The stretching temperature may vary according to the optical properties, mechanical properties and thickness required for the substrate film, the type of resin used, the thickness of the film used, the stretching method (uniaxial stretching or biaxial stretching), the stretching ratio, the stretching speed, etc. Specifically, the stretching temperature is preferably Tg~Tg+50°C, more preferably Tg+15°C~Tg+50°C, and most preferably Tg+35°C~Tg+50°C. By stretching at this temperature, a substrate film with appropriate properties can be obtained. The specific stretching temperature is, for example, 110°C~200°C, preferably 120°C~190°C, and more preferably 150°C~190°C.
[0063] The stretching ratio, like the stretching temperature, can vary according to the optical properties, mechanical properties and thickness, the type of resin used, the thickness of the film used, the stretching method (uniaxial stretching or biaxial stretching), the stretching temperature, the stretching speed, etc. When biaxial stretching is adopted, the ratio of the stretching ratio in the width direction (TD) to the stretching ratio in the length direction (MD) (TD / MD) is preferably 1.0 to 1.5, more preferably 1.0 to 1.4, and further preferably 1.0 to 1.3. Moreover, the surface ratio (the product of the stretching ratio in the length direction and the stretching ratio in the width direction) when biaxial stretching is adopted is preferably 2.0 to 6.0, more preferably 3.0 to 5.5, and further preferably 3.5 to 5.2.
[0064] The stretching speed and the stretching temperature can be changed according to the optical properties, mechanical properties and thickness, the type of resin used, the thickness of the film used, the stretching method (uniaxial stretching or biaxial stretching), the stretching temperature, the stretching ratio, etc. The stretching speed is preferably 3% / second to 20% / second, more preferably 3% / second to 15% / second, and further preferably 3% / second to 10% / second. When biaxial stretching is adopted, the stretching speed in one direction may be the same as or different from the stretching speed in the other direction.
[0065] [Adhesive layer]
[0066] The easy-adhesive layer contains a polycarbonate-based polyurethane having the properties described below as a main component. Here, the so-called "main component" means that among the components constituting the easy-adhesive layer, the constituent ratio is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and particularly preferably 95% by weight or more. The optical film of the present invention contains a polycarbonate-based polyurethane satisfying these properties as a main component in the easy-adhesive layer, which can suppress the initial performance reduction during long-term use under high temperature and high humidity, and at the same time, can suppress the whitening of the easy-adhesive layer and the reduction of optical properties due to extension, etc.
[0067] The preferred weight average molecular weight of polycarbonate polyurethane is 200,000 or more and 2,500,000 or less. The lower limit of the weight average molecular weight is preferably 250,000 or more, more preferably 300,000 or more, further preferably 400,000 or more, particularly preferably 500,000 or more, and most preferably 600,000 or more. The upper limit of the weight average molecular weight is preferably 2,200,000 or less, more preferably 2,000,000 or less, further preferably 1,900,000 or less, particularly preferably 1,800,000 or less, and most preferably 1,500,000 or less. When the weight average molecular weight does not reach 200,000, the initial adhesion with the acrylic resin film is poor, and the adhesion may be reduced when used for a long time under high temperature and high humidity. When the weight average molecular weight exceeds 2,500,000, it is difficult to manufacture a water-dispersible urethane resin. The reason is unclear, but it is speculated that polycarbonate polyurethane with a large molecular weight has a tendency to show a high entanglement density of the molecular chain and a high elastic modulus, so the tension resistance (tension caused by the material breaking due to stretching) is strong and the initial adhesion is excellent. In addition, it is estimated that polycarbonate polyurethane with a large molecular weight has a relatively large proportion of hard segments (crystalline parts) that contribute to adhesion, has high tensile strength, and suppresses hydrolysis under high temperature and high humidity. It should be noted that the weight average molecular weight of polycarbonate polyurethane can be measured by a conventionally known measurement method, for example, by gel permeation chromatography (GPC).
[0068] Shear storage elastic modulus (E') of the dry film of polycarbonate-based polyurethane at 25 °C 25 ) and the shear storage elastic modulus (E') at 85 °C 85 ) of the shear storage elastic modulus (E' 25 / E' 85 ) is preferably less than 5. Shear storage elastic modulus ratio (E' 25 / E' 85 ) is more preferably 4.5 or less, more preferably 4.0 or less, particularly preferably 3.5 or less, and most preferably 2.5 or less. The ratio of the shear storage elastic modulus at room temperature (25°C) to that at high temperature (85°C) (E' 25 / E' 85) is small, the initial adhesion to the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesive layer can be suppressed. Since the storage elastic modulus is an indicator of the hardness of the viscoelastic body, it is believed that the polycarbonate-based polyurethane with a small temperature dependence of the shear storage elastic modulus can suppress hydrolysis under high temperature and high humidity and maintain high tensile strength. In addition, it is believed that the polycarbonate-based polyurethane with a small temperature dependence of the shear storage elastic modulus has a wider allowable range for the load (stretching speed and stretching ratio) applied during thermal stretching, and suppresses whitening during stretching. In the present invention, by using a polycarbonate-based polyurethane that satisfies these characteristics, the initial adhesion to the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesive layer can be suppressed. The lower limit is not particularly limited, but is, for example, 0.1 or more, 0.5 or more. It should be noted that the shear storage elastic modulus (E') of the polycarbonate-based polyurethane at 25°C is 25 ) and the shear storage elastic modulus (E') at 85 °C 85 ) can be measured by a conventionally known measurement method, for example, by a dynamic viscoelasticity measurement (DMA) method.
[0069] Shear loss elastic modulus (E”) of dry film of polycarbonate polyurethane at 25°C 25 ) and shear loss elastic modulus (E') at 85°C 85 ) shear loss elastic modulus ratio (E') 25 / E” 85 ) is preferably less than 2. Shear loss elastic modulus ratio (E" 25 / E” 85 ) is more preferably 1.8 or less, further preferably 1.6 or less, particularly preferably 1.4 or less, and most preferably 1.2 or less. The ratio of the shear loss elastic modulus at room temperature (25°C) to that at high temperature (85°C) (E" 25 / E” 85 ) is smaller, the initial adhesion with the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesive layer can be suppressed. The lower limit is not particularly limited, but is, for example, 0.1 or more, 0.5 or more. It should be noted that the shear loss elastic modulus (E" at 25°C 25 ) and shear loss elastic modulus (E') at 85°C 85 ) can be determined by the above method.
[0070] Shear loss tangent (tanδ) of dry film of polycarbonate polyurethane at 25°C 25 ) is preferably 0.1 or less. Shear loss tangent (tanδ 25) is more preferably 0.09 or less, further preferably 0.08 or less, particularly preferably 0.07 or less, and most preferably 0.06 or less. The lower limit is not particularly limited, but is, for example, 0.01 or more. The shear loss tangent (tanδ) of the polycarbonate polyurethane at 85°C is 85 ) is preferably 0.5 or less. Shear loss tangent (tanδ 85 ) is preferably 0.4 or less, more preferably 0.3 or less, further preferably 0.25 or less, particularly preferably 0.2 or less, and most preferably 0.15 or less. The lower limit is not particularly limited, but is, for example, 0.01 or more, 0.05 or more. Shear loss tangent (tanδ 25 ) and shear loss tangent (tanδ 85 ) is within this range, the initial adhesion to the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the adhesive layer can be suppressed. It should be noted that the shear loss tangent (tanδ 25 ) and shear loss tangent (tanδ 85 ) can be determined by the above method.
[0071] Shear storage elastic modulus (E') of the dry film of polycarbonate polyurethane at 25°C 25 ) is preferably 500 MPa or more and 1500 MPa or less. The lower limit is more preferably 550 MPa or more, more preferably 600 MPa or more, particularly preferably 650 MPa, and most preferably 700 MPa. The upper limit is more preferably 1400 MPa, further preferably 1300 MPa, particularly preferably 1250 MPa, and most preferably 1200 MPa. In addition, the shear loss elastic modulus (E”) of polycarbonate polyurethane at 85°C 85 ) is preferably 80 MPa or more and 1000 MPa or less. The lower limit is more preferably 100 MPa or more, further preferably 150 MPa or more, particularly preferably 200 MPa or more, and most preferably 250 MPa or more. The upper limit is more preferably 900 MPa or less, further preferably 800 MPa or less, particularly preferably 700 MPa or less, and most preferably 600 MPa or less. Shear storage elastic modulus (E' 25 ) and shear loss elastic modulus (E” 85 ) within this range, the initial adhesion to the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesion layer can be suppressed.
[0072] Shear loss elastic modulus (E”) of dry film of polycarbonate polyurethane at 25°C 25) is preferably 40 MPa or more and 150 MPa or less. The lower limit is more preferably 45 MPa or more, further preferably 50 MPa or more, and particularly preferably 55 MPa or more. The upper limit is more preferably 130 MPa or less, further preferably 110 MPa or less, and particularly preferably 90 MPa or less. In addition, the shear loss elastic modulus (E”) of polycarbonate polyurethane at 85°C is 85 ) is preferably 20 MPa or more and 150 MPa or less. The lower limit is more preferably 25 MPa or more, further preferably 30 MPa or more, and particularly preferably 35 MPa or more. The upper limit is more preferably 130 MPa or less, further preferably 110 MPa or less, and particularly preferably 90 MPa or less. Shear loss elastic modulus (E" 25 ) and shear loss elastic modulus (E” 85 ) Within this range, the initial adhesion to the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesion layer can be suppressed.
[0073] The Tg of the polycarbonate polyurethane is preferably above 25°C and below 160°C. The lower limit is more preferably above 50°C, further preferably above 70°C, particularly preferably above 80°C, and most preferably above 100°C. The upper limit is more preferably below 150°C, further preferably below 145°C, and particularly preferably below 140°C. If Tg is within this range, the initial adhesion with the acrylic resin film is excellent, and the initial performance degradation under high temperature and high humidity and the whitening of the easy-adhesive layer can be suppressed. It should be noted that Tg can be measured by a conventionally known method, for example, the dynamic viscoelasticity is measured by a dynamic viscoelasticity measurement (DMA) method, and the temperature at which the shear loss tangent (tanδ) in the dynamic viscoelasticity becomes the maximum is set to Tg.
[0074] The Young's modulus of the dry film of polycarbonate polyurethane is preferably more than 400MPa and less than 1500MPa. The lower limit is more preferably more than 450MPa, more preferably more than 550MPa, and particularly preferably more than 650MPa. The upper limit is more preferably less than 1300MPa, more preferably less than 1100MPa, and particularly preferably less than 900MPa. If the Young's modulus of polycarbonate polyurethane is within this range, the initial adhesion with acrylic resin film is excellent, and the initial performance reduction under high temperature and high humidity and the whitening of the easy bonding layer can be suppressed.
[0075] The elongation at break of the dried film of the polycarbonate polyurethane is preferably less than 300%. The elongation at break is more preferably less than 250%, further preferably less than 200%, particularly preferably less than 100%, and most preferably less than 50%. If the elongation at break of the polycarbonate polyurethane is within this range, the initial adhesion with the acrylic resin film is excellent, and the initial performance reduction under high temperature and high humidity and the whitening of the easy-adhesive layer can be suppressed.
[0076] Polycarbonate polyurethane is a polyurethane having a carbonate skeleton in its molecular structure, and is a polyurethane obtained by reacting a polyisocyanate component having an average of 2 or more isocyanate groups in one molecule with a polycarbonate polyol component having an average of 2 or more hydroxyl groups in one molecule. Polycarbonate polyurethane is a linear urethane prepolymer obtained by reacting a polyisocyanate with a polycarbonate polyol in an organic solvent that is inert to isocyanate and miscible with water to form an isocyanate-terminated prepolymer, and then reacting with a chain extender having a free carboxyl group in water in the presence of a neutralizer, and extending the chain with water while being water-based. It can be obtained by adjusting the molecular weight, molar ratio, degree of polymerization, etc. of each component. It should be noted that the so-called water-based here means that the resin is stably dispersed or emulsified in water. Furthermore, the polycarbonate-based polyurethane preferably has a carboxyl group in the molecule. Having a carboxyl group provides excellent adhesion to an acrylic resin film and excellent adhesion to other components such as a polarizer.
[0077] Examples of polycarbonate polyols include those having the formula HO-R-(OC(O)-OR) X -OH (wherein, in the formula, R represents a saturated fatty acid polyol residue having 1 to 12 carbon atoms. And, X represents the number of structural units of the molecule, which is usually an integer of 5 to 50). These polycarbonate polyols can be obtained by, for example, an ester exchange method in which a saturated aliphatic polyol and a substituted carbonate are reacted under conditions of excess hydroxyl groups; a method in which a saturated aliphatic polyol is reacted with phosgene, or, as required, a saturated aliphatic polyol is subsequently reacted. In this case, as a substituted carbonate, for example, diethyl carbonate and diphenyl carbonate can be used. In addition, these can be used alone or in combination of two or more in any ratio.
[0078] Examples of polyisocyanates include aliphatic polyisocyanate compounds, alicyclic polyisocyanate compounds, and aromatic polyisocyanate compounds containing two or more isocyanate groups in one molecule. As aliphatic polyisocyanate compounds, aliphatic diisocyanates having 1 to 12 carbon atoms are preferred, such as hexamethylene diisocyanate, 2,2,4-trimethylhexane diisocyanate, hexane diisocyanate (HDI), etc. As alicyclic polyisocyanate compounds, alicyclic diisocyanates having 4 to 8 carbon atoms are preferred, such as 1,4-cyclohexane diisocyanate, methylcyclohexyl diisocyanate, isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI), etc. As aromatic polyisocyanate compounds, aromatic diisocyanates are preferred, such as toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate, xylene diisocyanate, etc. In addition, the polyisocyanate compound may be used individually by 1 type, and may use 2 or more types together in arbitrary ratios.
[0079] Examples of chain extenders having a free carboxyl group include dihydroxycarboxylic acids, dihydroxysuccinic acid, and the like. Examples of dihydroxycarboxylic acids include dihydroxyalkylalkanoic acids such as dimethylolalkanoic acid (e.g., dimethylolacetic acid, dimethylolbutyric acid, dimethylolpropionic acid, dimethylolbutyric acid, and dimethylolvaleric acid). These may be used alone or in combination of two or more.
[0080] Examples of the neutralizing agent include ammonia, N-methylmorpholine, triethylamine, dimethylethanolamine, methyldiethanolamine, triethanolamine, morpholine, tripropylamine, ethanolamine, triisopropanolamine, 2-amino-2-methyl-1-propanol, etc. These may be used alone or in combination of two or more.
[0081] In addition, other chain extenders that can be used include low molecular weight diol compounds such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, furandimethanol, diethylene glycol, triethylene glycol, and tetraethylene glycol, and polyether diol compounds obtained by addition polymerization of ethylene oxide, propylene oxide, tetrahydrofuran, etc. to these compounds; polyester diols having a hydroxyl group at the end obtained by reacting the above low molecular weight diol compounds with dicarboxylic acids such as succinic acid (anhydride), adipic acid (anhydride), and phthalic acid (anhydride), and their anhydrides; polyols such as trimethylolethane and trimethylolpropane; amino alcohols such as monoethanolamine, diethanolamine, and triethanolamine; diamine compounds such as ethylenediamine, propylenediamine, butanediamine, hexamethylenediamine, phenylenediamine, toluenediamine, xylene diamine, and isophorone diamine; water, ammonia, hydrazine, and dibasic acid hydrazide, etc. These can be used alone or in combination of two or more.
[0082] The acid value of the polycarbonate polyurethane is not particularly limited, but is preferably 50 mgKOH / g or less. The acid value is more preferably 5 mgKOH / g or more and 45 mgKOH / g or less, more preferably 15 mgKOH / g or more and 40 mgKOH / g or less, and particularly preferably 20 mgKOH / g or more and 35 mgKOH / g or less. If the acid value is within this range, the initial adhesion with the acrylic resin film is excellent, and the initial performance reduction under high temperature and high humidity and the whitening of the easy-adhesion layer can be suppressed.
[0083] The easy-adhesive layer may also contain resin components other than the above-mentioned polycarbonate-based polyurethanes within the scope of not hindering the effect of the present invention. As resin components other than the polycarbonate-based polyurethanes, for example, polyurethanes obtained by reacting a polyisocyanate component with a polyester polyol component, polyurethanes obtained by reacting a polyisocyanate component with a polyether polyol component, polyurethanes obtained by reacting a polyisocyanate component with a polyether·ester polyol component, polyurethanes obtained by reacting a polyisocyanate component with a polyacrylic polyol component, polyolefins, polyesters, acrylic polymers, etc. These can be used alone or in combination of two or more.
[0084] In the easy-adhesive layer, in order to improve the resistance to moisture and heat under high temperature and high humidity, a crosslinking agent may also be contained. As a crosslinking agent, any suitable crosslinking agent may be used, for example, urea compounds, epoxy compounds, melamine compounds, isocyanate compounds, oxazoline compounds, silanol compounds, carbodiimide compounds, etc. These can be used alone or in combination of two or more. The content of the crosslinking agent is not particularly limited, but is preferably 0.1 to 35 parts by weight relative to a total of 100 parts by weight of polycarbonate-based polyurethanes in terms of solid content conversion. More preferably 0.5 to 30 parts by weight, further preferably 3 to 25 parts by weight, particularly preferably 5 to 20 parts by weight. When containing resin components other than polycarbonate-based polyurethanes, as long as the crosslinking agent is deployed relative to 100 parts by weight of the solid content containing other resin components. It should be noted that when a crosslinking agent is deployed in the easy-adhesive layer, there is a possibility that the initial adhesion to the acrylic resin film is reduced. However, even if the crosslinking agent is not mixed, the polycarbonate polyurethane used in the present invention still has excellent initial adhesion with the acrylic resin film, and can suppress initial performance degradation and whitening of the easy-adhesive layer under high temperature and high humidity, so the mixing amount of the crosslinking agent can be within a very small range. Specifically, the mixing amount of the crosslinking agent is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, and particularly preferably 0.5 parts by weight or less, relative to a total of 100 parts by weight of the polycarbonate polyurethane.
[0085] The easy-adhesion layer may also contain any suitable microparticles in accordance with the function. And preferably water-dispersible microparticles. As microparticles, inorganic microparticles include inorganic oxides such as silicon oxide, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. As organic microparticles, for example, silicone resins, fluorine resins, (meth) acrylic resins, (meth) acrylonitrile resins, etc. Among these, silicon oxide is preferred. Since silicon oxide microparticles have excellent adhesion inhibition and excellent transparency, do not produce haze and coloring, the easy-adhesion layer has less influence on optical properties.
[0086] The average particle size of the microparticles is not particularly limited, but based on the viewpoint of maintaining the transparency of the easy-adhesion layer, it is preferably 1 to 500 nm, more preferably 5 to 300 nm, and further preferably 100 to 100 nm. By using microparticles having these particle sizes, it is possible to appropriately form concavities and convexities on the surface of the easy-adhesion layer, effectively reduce the friction between the contact surfaces of the resin film and the easy-adhesion layer and / or the easy-adhesion layers, and inhibit adhesion.
[0087] The adhesive layer may further contain any appropriate additives, such as dispersion stabilizers, thixotropic agents, antioxidants, ultraviolet absorbers, defoamers, thickeners, dispersants, surfactants, catalysts, lubricants, antistatic agents, and the like.
[0088] The thickness of the easy-adhesive layer is not particularly limited, but is preferably, for example, 0.01 μm or more and 10 μm or less. The lower limit is more preferably 0.03 μm or more, further preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and most preferably 0.15 μm or more, and the upper limit is more preferably 3 μm or less, further preferably 2 μm or less, particularly preferably 1 μm or less, and most preferably 0.5 μm or less. By setting the thickness of the easy-adhesive layer to the above range, the adhesion can be effectively improved.
[0089] [Optical Film]
[0090] Figure 1 An example of the optical film of the present invention is shown. Figure 1 The optical film 1 shown is a resin film 2 containing an acrylic resin as a main component, and has an easy-adhesion layer 3 containing a polycarbonate polyurethane as a main component on one surface of the resin film 2. The specific structure of the resin film 2 and the easy-adhesion layer 3 is as described above. It should be noted that the easy-adhesion layer 3 only needs to be formed on at least one surface of the resin film 2, and can also be formed on both surfaces of the resin film 2.
[0091] Based on the viewpoint of stably exerting the function as an optical component, the total light transmittance of the optical film is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The light transmittance can be measured according to JIS K0115 using a spectrophotometer (manufactured by JASCO Corporation, ultraviolet visible light near infrared spectrophotometer "V-570").
[0092] The haze of the optical film is not particularly limited, but is preferably 2.0% or less, more preferably 1.0% or less, further preferably 0.8% or less, and particularly preferably 0.5% or less. The haze can be measured in accordance with JIS K7361-1997 using a turbidimeter NDH-300A manufactured by Nippon Denshoku Industries.
[0093] The total thickness of the optical film is preferably 5 μm or more, more preferably 8 μm or more, further preferably 10 μm or more, preferably 200 μm or less, more preferably 100 μm or less, and particularly preferably 70 μm or less. By setting the total thickness of the optical film to be above the lower limit, the mechanical strength of the optical film can be improved. In addition, by setting it to be below the upper limit, the thickness of the entire optical film can be reduced.
[0094] In the optical film of the present invention, various functional layers may be formed on the surface opposite to the surface on which the easy-adhesion layer is formed as required. Examples of the functional layer include an antistatic layer, an adhesive layer, an adhesive layer, an easy-adhesion layer, an anti-glare (non-glare) layer, an anti-fouling layer such as a photocatalyst layer, an anti-reflection layer, a hard coating layer, an ultraviolet shielding layer, a heat shielding layer, an electromagnetic wave shielding layer, a gas barrier layer, and the like.
[0095] The optical film of the present invention is, for example, a polarizer protective film, a phase difference film, a viewing angle compensation film, a light diffusion film, a reflective film, an anti-reflective film, an anti-glare film, a brightness enhancement film, a conductive film for a touch panel, etc. The optical film of the present invention may be an optically isotropic film or an optically anisotropic film (for example, a film exhibiting birefringence such as phase difference).
[0096] [Method for producing optical film]
[0097] The method for producing an optical film of the present invention comprises the following steps: a step of applying a coating liquid containing an aqueous solvent and a polycarbonate-based polyurethane to at least one surface of a resin film containing an acrylic resin as a main component to form a coating film, and a step of drying or curing the coating film to form an easy-adhesion layer. Preferably, the optical film is produced by the following first production method or second production method.
[0098] [First Manufacturing Method]
[0099] The first method for manufacturing a preferred optical film of the present invention comprises the following steps: a step of applying a coating liquid containing an aqueous solvent and a polycarbonate-based polyurethane to at least one surface of a pre-stretched resin film composed of a thermoplastic resin containing an acrylic resin as a main component to form a coating film, a step of drying or curing the coating film to form an easy-to-adhesive layer, and a step of stretching the pre-stretched resin film to obtain a stretched film.
[0100] In the first method for producing an optical film of the present invention, a step of preparing a pre-stretched resin film is performed. The pre-stretched resin film is a raw film to be a stretched film by stretching treatment, and is made of a thermoplastic resin containing an acrylic resin as a main component.
[0101] In order to improve the adhesion between the resin film and the easy-adhesion layer, the surface of the resin film before the extension of the coating film can also be subjected to surface modification. The surface modification treatment usually improves the hydrophilicity of the treated surface, and the average water contact angle of the surface and the standard deviation of the water contact angle are set to the desired range. The range of the desired average water contact angle is preferably 20°~80°, more preferably 20°~75°, and further preferably 20°~50°. Examples of surface modification treatment include, for example, radiation irradiation treatment and chemical treatment. Examples of radiation irradiation treatment include, for example, corona discharge treatment, liquid crystal treatment, electron beam irradiation treatment, ultraviolet irradiation treatment, etc., and based on the aspects of treatment efficiency, etc., preferably corona discharge treatment and liquid crystal treatment, particularly preferably corona discharge treatment. And examples of chemical treatment include, for example, saponification treatment and immersing the film in an aqueous oxidant solution such as potassium dichromate solution and concentrated sulfuric acid, followed by water washing.
[0102] In the first manufacturing method, a coating liquid containing an aqueous solvent and a polycarbonate-based polyurethane is applied to at least one side of the resin film before stretching to form a coating film. The method for forming the coating film on the resin film before stretching is not particularly limited, but examples of coating methods include wire bar coating, dipping, spraying, spin coating, roll coating, gravure coating, air knife coating, curtain coating, slide coating, extrusion coating, and the like.
[0103] In the first manufacturing method, after forming a coating film on the surface of the resin film before stretching, the coating film is dried or cured to obtain a step of an easy-adhesive layer. The coating film is usually cured by drying the solvent contained in the coating solution. At this time, based on the viewpoint of making the coating film rapidly carry out a cross-linking reaction or the like, it is preferably heat-treated. The heating temperature and the heating time can be appropriately set in the range in which the desired reaction of the processing reaction or the like is carried out.
[0104] In the first production method, after forming the easy-adhesion layer on the surface of the resin film before stretching, the resin film before stretching is stretched to obtain a stretched film. As the stretching method, the above-mentioned stretching method can be used.
[0105] In the first manufacturing method, the step of drying or curing the coating film to obtain an easy-adhesive layer and the step of extending the pre-stretched resin film to obtain a stretched film, either step can be performed first, or both steps can be performed simultaneously. Based on the viewpoint of improving the adhesion between the stretched film and the easy-adhesive layer, it is preferred to simultaneously perform the step of drying or curing the coating film to obtain an easy-adhesive layer and the step of extending the pre-stretched resin film to obtain a stretched film. When the two steps are performed simultaneously, the coating film is usually dried or cured by heating the coating film with the heat applied when the pre-stretched resin film is stretched. By performing the above steps, an optical film having a stretched film and an easy-adhesive layer provided on at least one side of the stretched film is obtained.
[0106] From the viewpoint of improving the manufacturing efficiency of the optical film, it is preferred to manufacture the optical film as a long film. When manufacturing the optical film as a long film, it is preferred to prepare a long strip of pre-stretched resin film, and while conveying the pre-stretched resin film in the length direction, a coating liquid containing polycarbonate-based polyurethane is applied to the surface of the pre-stretched resin film, and the easy-adhesive layer is continuously formed by drying or curing. For example, before the continuously conveyed long strip of pre-stretched resin film is supplied to the stretching device, the surface of the pre-stretched resin film is coated with the coating liquid, and the coating film is dried and the pre-stretched resin film is stretched in the preheating zone and the stretching zone of the stretching device at the same time.
[0107] [Second Manufacturing Method]
[0108] The second preferred method for manufacturing an optical film of the present invention comprises the following steps: a step of applying a coating liquid containing an aqueous solvent and a polycarbonate-based polyurethane to at least one surface of a stretched film composed of a thermoplastic resin containing an acrylic resin as a main component to form a coating film, and a step of drying or curing the coating film to form an easy-to-adhesive layer.
[0109] In the second method for manufacturing an optical film of the present invention, a step of preparing a stretched film is performed. The stretched film can be manufactured by a manufacturing method including a step of preparing a pre-stretched resin film and stretching the prepared pre-stretched resin film to obtain a stretched film, as described in the first manufacturing method. In addition, the surface of the stretched film formed with the coating film may be subjected to the above-mentioned surface modification treatment in order to improve the adhesion between the stretched film and the easy-adhesion layer.
[0110] Next, a coating liquid containing an aqueous solvent and a polycarbonate-based polyurethane is applied to at least one surface of the stretched film to form a coating film. As the coating method, the above-mentioned coating method can be used.
[0111] Subsequently, the easy-adhesion layer is obtained by drying or curing the coating liquid layer formed on the surface of the stretched film. At this time, the coating film is usually cured by drying the solvent contained in the coating liquid. During this curing, it is preferably heated.
[0112] By performing the above steps, an optical film having a stretched film and an easy-adhesion layer provided on at least one side of the stretched film is obtained. As in the first manufacturing method, in the second manufacturing method, the optical film is preferably manufactured as a long film from the viewpoint of improving the manufacturing efficiency of the optical film.
[0113] [Polarizing plate]
[0114] Hereinafter, a polarizing plate will be described as an example of the optical member of the present invention. Figure 2 A polarizing plate which is an example of the optical member of the present invention is shown. Figure 2 The polarizing plate 10 shown has a structure in which an optical film 4 having an easy-adhesion layer 3 having a polycarbonate-based polyurethane as a main component is provided on one surface of a resin film 2 having an acrylic resin as a main component, and a polarizer 6 is laminated on the surface on the easy-adhesion layer side thereof via an adhesive 5. It should be noted that, although not shown in the figure, another polarizer protective film or a phase difference film, etc., laminated via an adhesive layer, may be provided on the opposite side of the polarizer from the optical film.
[0115] The polarizing plate has a structure in which a polarizer is laminated on the surface of an optical film having an easy-adhesion layer on the surface of a resin film containing an acrylic resin as a main component, and an adhesive layer is interposed between the surface of the easy-adhesion layer of the optical film. The easy-adhesion layer formed on the optical film has excellent strength and easy adhesion, so the polarizing plate can be excellent in adhesion between the polarizer and the optical film.
[0116] As a polarizer, any appropriate polarizer can be used according to the purpose. For example, hydrophilic polymer films such as polyvinyl alcohol films, partially formaldehyde-treated polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers, polyolefin-based oriented films that adsorb dichroic substances such as iodine or dichroic dyes and uniaxially stretch, dehydrated products of polyvinyl alcohol, or dehydrochlorinated products of polyvinyl chloride, etc., are exemplified. Among these, polarizers that adsorb dichroic substances such as iodine on polyvinyl alcohol films and uniaxially stretch are particularly preferred because of their high polarization dichroic ratio. The thickness of these polarizers is not particularly limited, but is generally about 1 to 80 μm.
[0117] Any appropriate adhesive can be used as the adhesive forming the adhesive layer. The adhesive layer is preferably formed of an adhesive composition containing a polyvinyl alcohol-based resin or an ultraviolet curable adhesive composition containing an acrylic resin.
[0118] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples.
[0119] The following materials were used as raw materials. Table 1 shows the property values of the water-dispersible urethane resin, including weight average molecular weight, shear storage modulus, shear loss modulus, and shear loss tangent.
[0120] <Water-dispersible urethane resin>
[0121] · Water-dispersible urethane resin emulsion (1) [Polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-5, solid content 30 wt %]
[0122] · Emulsion of water-dispersible urethane resin (2) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-6, solid content 30 wt %]
[0123] · Emulsion of water-dispersible urethane resin (3) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-7, solid content 30 wt %]
[0124] · Emulsion of water-dispersible urethane resin (4) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-8, solid content 30 wt %]
[0125] · Emulsion of water-dispersible urethane resin (5) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-9, solid content 30 wt %]
[0126] · Emulsion of water-dispersible urethane resin (6) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-10, solid content 30 wt %]
[0127] · Emulsion of water-dispersible urethane resin (7) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-11, solid content 30 wt %]
[0128] · Emulsion of water-dispersible urethane resin (8) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-2, solid content 30 wt %]
[0129] · Emulsion of water-dispersible urethane resin (9) [polycarbonate polyurethane, manufactured by ADEKA Corporation, SPX-1139-3, solid content 30 wt %]
[0130] · Emulsion of water-dispersible urethane resin (10) [Polyester polyurethane, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Superflex (registered trademark) 210, solid content 35 wt %]
[0131] [Weight average molecular weight (Mw)]
[0132] The weight average molecular weight (Mw) of the water-dispersible urethane resin was measured using a gel permeation chromatography (GPC) device under the following conditions. The sample solution was prepared by adding 5 ml of solvent to 17 mg of the sample, stirring gently at room temperature to confirm dissolution, and then filtering using a 0.45 μm filter. It should be noted that Mw was calculated based on standard polystyrene conversion.
[0133] Equipment used: Liquid chromatograph (Shimadzu Corporation, LC-2030Plus)
[0134] Detector: Differential refractive index detector RI (made by Shimadzu Corporation, RID-20A, sensitivity 32)
[0135] Column: TSKgelα-M (φ7.8mm×300mm, manufactured by TOSOH)
[0136] Solvent: Dimethylformamide (DMF) with 0.02M lithium chloride added
[0137] Flow rate: 0.8ml / min
[0138] Column temperature: 40℃
[0139] Injection volume: 0.1ml
[0140] Standard sample: Monodisperse polystyrene manufactured by TOSOH
[0141] Data processing: GPC data processing system manufactured by TRC
[0142] [Dynamic viscoelasticity (DMA)]
[0143] The shear storage elastic modulus (E'), shear loss elastic modulus (E"), and shear loss tangent (tanδ) of the water-dispersible urethane resin were measured by the following method. First, the water-dispersible emulsion was dispensed into a container such as a petri dish and dried in such a manner that the film thickness after drying became 300 μm, and a polyurethane film was prepared, which was then cut into a length of 40 mm × a width of 10 mm to obtain a sample for measurement. Next, a dynamic viscoelasticity measuring device (manufactured by Hitachi High-Technologies Co., Ltd., model: DMA7100) was used, and the distance between the clamps was set to 20 mm in the tensile mode. The temperature was raised at a constant frequency (1 Hz) at 2°C / min, and the measurement was performed in a temperature range of -50 to 160°C.
[0144]
[0145] (Manufacturing of easy-adhesion composition)
[0146] Each component shown in Table 1 was prepared using ion-exchanged water so that the solid content was 8% by weight to produce an easy-adhesion composition.
[0147] (Example 1)
[0148] The pellets of acrylic resin [Tg: 122°C, melt viscosity: 1000 Pa·s (temperature 260°C, shear rate 100 (1 / sec))] were melt-extruded at 260°C using a uniaxial extruder (φ=40.0mm, L / D=32) and a hanger-type T-die (width 500mm), and the molten resin was sprayed onto a cooling roll maintained at 100°C to form an acrylic resin film with a thickness of 100μm. Next, the easy-adhesion composition obtained above was applied to one surface of the acrylic resin film using a rod coater, and then placed in a hot air dryer and dried at 100°C for 90 seconds. After bonding, the film was subjected to fixed-end uniaxial stretching (stretching temperature: 145°C, stretching ratio: 3.0 times) using a desktop stretching machine to produce an optical film having an easy-adhesion layer with a thickness of 0.3μm on the surface of a methacrylic resin film with a thickness of 40μm.
[0149] (Examples 2 to 4, Comparative Examples 1 to 3)
[0150] An optical film was produced under the same conditions as in Example 1 except that the easy-adhesion composition shown in Table 2 was used.
[0151] (Comparative Examples 4 and 5)
[0152] An optical film was produced under the same conditions as in Example 1 except that the easily adhesive composition shown in Table 2 was used and the thickness of the easily adhesive layer was changed to 0.2 μm.
[0153] (Reference example)
[0154] An optical film was produced under the same conditions as in Example 1 except that the easily adhesive composition shown in Table 2 was used and the thickness of the easily adhesive layer was changed to 0.2 μm.
[0155] The optical films obtained in Examples, Comparative Examples, and Reference Examples were evaluated as follows.
[0156] [Initial adhesion]
[0157] A polyvinyl alcohol-based adhesive composition ("Gosenex (registered trademark) Z-200" manufactured by Mitsubishi Chemical Co., Ltd.) is applied to the easy-adhesive layer side of the optical film obtained in the examples, comparative examples, and reference examples, and after laminating with an iodine-based polarizer having a thickness of 60 μm through the adhesive composition, it is placed in a hot air dryer (80°C) and dried for 10 minutes to obtain a laminate bonded to the polarizer. A sample piece of 25 mm × 250 mm in size is cut out from the laminate obtained above, and an adhesive process is performed on the surface of the optical film, and it is attached to a glass plate. Subsequently, the polarizer of the laminate is pinched, and the 90-degree peel strength is measured according to the floating roller method of Japanese Adhesive Industry Standard JAI13-1996. The unit of peel strength is expressed as (N / 25 mm).
[0158] [Moisture and heat resistance (85°C, 85%RH)]
[0159] A polyvinyl alcohol-based adhesive composition ("Gosenex (registered trademark) Z-200" manufactured by Mitsubishi Chemical Co., Ltd.) is applied to the easy-adhesive layer side of the optical film obtained in the examples, comparative examples and reference examples, and after laminating with an iodine-based polarizer having a thickness of 60 μm through the adhesive composition, the laminate is placed in a hot air dryer (80° C.) and dried for 10 minutes to obtain a laminate bonded to the polarizer. Next, the laminate is placed in a constant temperature and humidity machine at a temperature of 85° C. and a humidity of 85% RH. After being placed for 240 hours, the laminate is taken out and placed at room temperature for 12 hours. For bonding, a sample piece of 25 mm × 250 mm in size is cut out from the laminate obtained above, and an adhesive process is performed on the surface of the optical film. After being attached to a glass plate, the polarizer of the laminate is pinched, and the 90-degree peel strength is measured according to the floating roller method of Japanese Adhesive Industry Standard JAI13-1996. The unit of peel strength is expressed as (N / 25 mm).
[0160] [Optical properties]
[0161] The appearance of the optical films obtained in Examples, Comparative Examples, and Reference Examples was visually evaluated. The evaluation criteria are as follows.
[0162] ◎: The adhesive layer does not change before and after the optical film is stretched, and the adhesive layer of the stretched optical film does not whiten.
[0163] △: Before and after the optical film is stretched, the adhesive layer is slightly changed. After stretching, the adhesive layer of the optical film is slightly whitened.
[0164] ×: The adhesive layer changes before and after the optical film is stretched, and whitening is observed in the adhesive layer of the stretched optical film.
[0165]
[0166] As shown in Table 2, the weight average molecular weight of the composite was 200,000 or more and 2,500,000 or less, and the shear storage modulus (E') at 25°C was 250,000 or less. 25 ) and shear storage elastic modulus (E') at 85°C 85 ) shear storage elastic modulus ratio (E' 25 / E' 85 ) is less than 5, the optical films of Examples 1 to 4 of the easy-adhesive layer of polycarbonate-based polyurethane show excellent initial adhesion and adhesion during long-term use in a high-temperature and high-humidity environment, and no whitening of the easy-adhesive layer due to stretching is observed, showing excellent optical properties.
[0167] On the other hand, as shown in Table 2, the optical films of Comparative Examples 1 to 4 using an easy-adhesive layer containing a polycarbonate-based polyurethane with a weight average molecular weight of 10,000 to 30,000 showed poor adhesion during long-term use under high temperature and high humidity, and the easy-adhesive layer was whitened due to extension. The optical film of Comparative Example 5 using an easy-adhesive layer containing a polycarbonate-based polyurethane with a weight average molecular weight of 30,000 to 100,000 showed poor adhesion during long-term use under high temperature and high humidity, and the easy-adhesive layer was whitened due to extension. It should be noted that even the optical film of the reference example using an easy-adhesive layer containing a polyester-based polyurethane showed poor adhesion during long-term use under high temperature and high humidity, although the initial adhesion was the same as that of the examples.
[0168] Description of Reference Numerals
[0169] 1: optical film; 2: resin film; 3: easy-adhesion layer; 4: optical film; 5: adhesive layer; 6: polarizer; 10: polarizing plate.
Claims
1. An optical film, characterized in that: The optical film comprises: a resin film containing an acrylic resin as a main component; and an easy-adhesion layer laminated on one surface of the resin film, wherein the easy-adhesion layer contains a polycarbonate polyurethane as a main component, wherein the weight average molecular weight of the polycarbonate polyurethane is greater than or equal to 200,000 and less than or equal to 2.5 million, and the shear storage elastic modulus E' at 25°C is less than or equal to 100%. 25 Shear storage elastic modulus E' at 85°C 85 Shear storage elastic modulus ratio E' 25 / E' 85 Is 5 or less.
2. The optical film according to claim 1, characterized in that: The shear loss elastic modulus E of the polycarbonate polyurethane at 25°C 25 Shear loss elastic modulus E' at 85°C 85 Shear loss elastic modulus ratio E' 25 / E” 85 Is less than 2.
3. The optical film according to claim 1, characterized in that: The shear loss tangent tanδ of the polycarbonate polyurethane at 25°C 25 Is less than 0.
1.
4. The optical film according to claim 1, characterized in that: The shear storage elastic modulus E' of the polycarbonate polyurethane at 25°C 25 It is 500 MPa or more and 1500 MPa or less.
5. The optical film according to claim 1, characterized in that: The shear loss elastic modulus E of the polycarbonate polyurethane at 25°C 25 It is 40 MPa or more and 150 MPa or less.
6. The optical film according to claim 1, characterized in that: The acrylic resin has at least one selected from the group consisting of a glutarimide unit, a lactone ring unit, a maleic anhydride unit, a maleimide unit, and a glutaric anhydride unit.
7. A polarizing plate, characterized in that: The polarizing plate is formed by laminating the optical film according to any one of claims 1 to 6, an adhesive layer, and a polarizer in this order such that the easy-adhesion layer is in contact with the adhesive layer.
Citation Information
Patent Citations
Method for producing imide polymer
JP2005023272A
Polarizer protection film, polarizing plate and image display device
JP2008181078A
Endoscope
JP2010063773A
Polarizer protection film and polarizing plate
JP2016033552A
Imide resin, and production method and use thereof
WO2005054311A1